Novel Exact and Solitary Wave Solutions for The Time-Fractional Nonlinear Maccari's System (Contemporary Mathematics, 2023)
The purpose of this research is to find analytical solutions to the time-fractional nonlinear Maccari system. The double auxiliary equation method, which has never been used before, is used to obtain these solutions. The method is cleverly applied, resulting in the generation of nine new exact solitary wave solutions that have never been found before. We also describe the system’s dynamic behavior and the bifurcation of traveling waves. Finally, we show some solutions with different coefficient values that correspond to the nine discovered solutions graphically.
Keywords: three coupled Maccari system; the double auxiliary equation method; bifurcation; conformable fractional derivative; exact solutions